2009
DOI: 10.1103/physrevlett.103.175002
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Saturation of Convective Modes of the Two-Plasmon Decay Instability in Inertial Confinement Fusion

Abstract: Particle-in-cell (PIC) and fluid simulations of two-plasmon decay (TPD) instability under conditions relevant to inertial confinement fusion show the importance of convective modes. Growing at the lower density region, the convective modes can cause pump depletion and are energetically dominant in the nonlinear stage. The PIC simulations show that TPD saturates due to ion density fluctuations, which can turn off TPD by raising the instability threshold through mode coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 15 publications
3
39
0
Order By: Relevance
“…The large fraction of laser energy converted into hot electrons and its observed saturation, is a direct consequence of the simultaneous high intensity and long-scale lengths produced in these experiments. ZAK [13] which solves the equations of the extended Zakharov model [14]. The saturating nonlinearities included in the model are density profile modification [29], Langmuir wave cavitation [30], and the generation of ion acoustic turbulence [13,15].…”
mentioning
confidence: 99%
“…The large fraction of laser energy converted into hot electrons and its observed saturation, is a direct consequence of the simultaneous high intensity and long-scale lengths produced in these experiments. ZAK [13] which solves the equations of the extended Zakharov model [14]. The saturating nonlinearities included in the model are density profile modification [29], Langmuir wave cavitation [30], and the generation of ion acoustic turbulence [13,15].…”
mentioning
confidence: 99%
“…In the linear regime, the growth rates and thresholds predicted by the linear theories were examined in both PIC and fluid simulations. Pump depletion and convective modes' domination were observed in the well-above-threshold PIC simulations [9]. The PIC simulations showed that both the absolute and convective modes saturate due to ion density fluctuations, which can turn off TPD by raising the instability threshold through mode coupling and lead to intermittent growth [9].…”
Section: Two-plasmon Decay Instability and Energetic Electron Generatmentioning
confidence: 96%
“…Pump depletion and convective modes' domination were observed in the well-above-threshold PIC simulations [9]. The PIC simulations showed that both the absolute and convective modes saturate due to ion density fluctuations, which can turn off TPD by raising the instability threshold through mode coupling and lead to intermittent growth [9]. A series of PIC simulations were performed on the long-term (~10 ps) nonlinear behaviors of the TPD instability [18].…”
Section: Two-plasmon Decay Instability and Energetic Electron Generatmentioning
confidence: 99%
See 2 more Smart Citations